PENERAPAN MODEL MORAL REASONING UNTUK MEMBENTUK MORALITAS DAN KARAKTER SISWA PADA PKn - Mukino Mukino; Eddy Purnomo; Irawan Suntoro (Jurnal Studi Sosial / Journal of Social Studies, 2016)
The objective of this research was to explain how lesson plan works, including the evaluation system in the application of moral reasoning model to build students morality and character. The method used in this research was classroom action research with cycles and the stages are planning, implementation, observation and reflection. The results of the research are as follows: The implementation of the lesson plan using moral reasoning model with the stages planned showed a tendency to be better. Even at the third stage, the result had showed the intended success. The application of moral reasoning after being revised through appropriate stages and cycles would be effective in increasing students morality. This was proved by the result of the research: first stage tend to be less effective, then second stage showed quite effectivity, and finally the third stage showed to be effective. Then, this moral reasoning model could also be used to increase students character. After being revised through appropriate stages and cycles would be effective in increasing students character.Tujuan dari penelitian ini adalah untuk menjelaskan RPP, pelaksanaan pembelajaran, dan sistem evaluasi dalam menerapkan model pembelajaran moral reasoning yang dapat membentuk moralitas dan karakter siswa. Metode yang digunakan pada penelitian ini adalah PTK. Hasil penelitian dapat diuraikan sebagai berikut; Penerapan Rencana Pelaksanaan Pembelajaran dengan menggunakan model pembelajaran moral reasoning yang dilaksanakan sesuai dengan tahap-tahap yang telah ditentukan, pada setiap siklusnya cenderung mengalami peningkatan kearah yang lebih baik, bahkan pada siklus ke III telah mencapai indikator keberhasilan yang telah ditetapkan. Penerapan model moral reasoning yang dilaksanakan dengan langkah-langkah yang benar dan setiap siklusnya melakukan perubahan yang baik akan efektif untuk meningkatkan moralitas siswa.Kata kunci: karakter, moralitas, moral reasoning